A study on signature analyzer for design for test (DFT) - A'ain, Abu Khari; Lim, C. T.; Kok, Hong Ng; Sheng, Kwang Ng; Liew, Eng Yew (IEEE, 2004)
This paper takes a look at the use of linear feedback shift registers (LFSR's) as test pattern generators (TPG's) and signature analyzers for built-in self-test (BIST). We also propose a method to generate pseudorandom test patterns. The proposed method can generate longer sequences of the same set of test patterns.